Mitigating cross-site scripting attacks with a content security Policy - Yusof, Imran; Pathan, Al Sakib Khan (IEEE Computer Society, 2016)
A content security policy (CSP) can help Web application developers and server administrators better control website content and avoid vulnerabilities to cross-site scripting (XSS). In experiments with a prototype website, the authors' CSP implementation successfully mitigated all XSS attack types in four popular browsers.